Using Pedagogical Practices in an Online Learning Environment to Enhance Motivation and Self-directed Learning of Part-time Students - Trinidad, Sue; Fox, R. (2006)
Part-time students, working full-time have many problems that need to be addressed while juggling work, study and home commitments. Assumptions about student motivation and how they handle their busy lifestyle need to be factored into study routines and curriculum structures. This research investigated the factors affecting full-time teacher progress in undertaking a tertiary part-time course. Using an action research methodology and an online learning management system to support pedagogical practices, two University of Hong Kong instructors attempted to help their students take responsibility for their own learning and develop appropriate self-directed learning abilities in two consecutive modules using a combination of flexible learning, face-to-face and e-learning strategies. The findings have verified the attempts to better tailor teaching and learning to meet students' needs and also have been informative for other part-time undergraduate programmes. The results support the need for strategies to accommodate an expected increase in part-time tertiary students who are also working full time.